2001
DOI: 10.1007/s004210100401
|View full text |Cite
|
Sign up to set email alerts
|

Muscular co-operation during joint stabilisation, as reflected by EMG

Abstract: The experiment that was carried out consisted of subjects pushing an external object (a heavy pendulum) using stable and unstable handles of increasing mobility. Using this protocol it was possible to distinguish between the motor and stabilising functions of the muscles of the upper extremity. The motor functions were realised by the extensors of the upper extremity, whereas stabilising functions were effected by the muscles spanning the wrist joint. The experiment involved synchronised measurements of the el… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

5
32
0
2

Year Published

2003
2003
2021
2021

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 37 publications
(39 citation statements)
references
References 7 publications
5
32
0
2
Order By: Relevance
“…Furthermore, the GM showed patterns, which depended on the dynamic aspects of the movement, reflected in similar delayed onsets of activity in the dynamic conditions (1 and 3 DoF) as compared to the static 0 DoF condition. This sequence is in accordance to studies on the wrist (Kornecki et al, 2001) confirming the idea that not the mobility of the object being set in motion influences the forces produced by individual muscles. Especially multiarticular muscles like the GM bear multiple functions since they operate at several joints and thus develop different torques at the spanned joints simultaneously (Kornecki et al, 2001;van Ingen Schenau et al, 1987).…”
Section: Altered Muscle Activation Patterns Due To Changing Environmesupporting
confidence: 90%
See 3 more Smart Citations
“…Furthermore, the GM showed patterns, which depended on the dynamic aspects of the movement, reflected in similar delayed onsets of activity in the dynamic conditions (1 and 3 DoF) as compared to the static 0 DoF condition. This sequence is in accordance to studies on the wrist (Kornecki et al, 2001) confirming the idea that not the mobility of the object being set in motion influences the forces produced by individual muscles. Especially multiarticular muscles like the GM bear multiple functions since they operate at several joints and thus develop different torques at the spanned joints simultaneously (Kornecki et al, 2001;van Ingen Schenau et al, 1987).…”
Section: Altered Muscle Activation Patterns Due To Changing Environmesupporting
confidence: 90%
“…This resulted in an advanced onset of stabilizing muscles relative to force producing muscles (Kornecki et al, 2001). These adjustments to changing biomechanical task demands arise, since muscles can cause destabilizing or counterproductive movements at some joints when they are contracted to create desired movements at other joints (Kornecki et al, 2001). In order to control the forces produced by muscles during movement only a certain fraction of the possibly available mobility of the motor system is needed at a given time (Kornecki 1992).…”
Section: Introductionmentioning
confidence: 98%
See 2 more Smart Citations
“…It has been concluded that performing exercises on unstable surfaces enhances joint stabilization by increasing the synergy between muscles (Anderson, 2004). Furthermore, Kornecki et al (2001) emphasized the importance of increased stabilization functions for performing voluntary and coordinated movements. In this regard, the positive impact of functional balance training on training group seemed to transfer the force produced by muscles to the ball rather than stabilizing posture.…”
Section: Discussionmentioning
confidence: 99%